Professional Empowerment Strategies of Nepali English language Teacher: A grand Narrative - Banjade, Nilam (Resunga Journal रेसुङ्गा जर्नल, 2024)
This present paper aimed to explore professional empowering strategies of secondary English language teachers using a grand narrative inquiry method. For this study, interview was used to gather the grand narratives of four English language teachers. The critical events from their sharing were taken as authentic information and analyzed using transformative lens. The findings show that language teachers have become professionally more conscious, optimistic, updated, and transformative to accept the dynamic settings of English language teaching through building connection with language associations, social media messenger, workshop, seminar, and collaboration and sharing for empowering their skill. The findings also showed that the teachers respect the voices of the learners as the sources of imparting teaching learning skills and knowledge for professional enrichment.